Edukasi “Satu Piring Cegah Stunting” sebagai Upaya Preventif bagi Anak dengan Waspada Stunting di Desa Sawaran Lor, Kabupaten Lumajang - Mahfudloh, Filla Apriliani; Qoirunnasikin, Liwa; Kirana, Mutiara Nasywa; Safitri, Puput Linanda; Maghfiroh, Fitrah Ainun; Ardilla, Yunita (CV. ULIL ALBAB CORP, 2025)
A condition where a child experiences chronic malnutrition which results in height growth that is not optimal according to age is a symptom of stunting. According to Basic Health Research (Riskesdas) data, the prevalence of stunting in Indonesia is still quite high, reaching 21.5%, while the government targets it to reach 14% by 2024. Efforts are being made to prevent the emergence of symptoms of stunting, especially in Sawaran Lor Village, Lumajang Regency is providing education regarding stunting prevention by utilizing print media in the form of brochures. Taking the theme